المعجم الجزائري بين الوضع والرقمنة - بن شني, أحمد (كلية الأدب العربي والفنون, 2024)
تهدف هذه الدراسة الموسومة ب " المعجم الجزائري بين الوضع والرقمنة -معجم الثقافة الجزائرية نموذجا - إلى بيان مدى أهمية المعجم في اللغة العربية وفي الحفاظ على الموروثات الأدبية واللغوية والثقافية والحضارية،فقد سعى المجلس الأعلى للغة العربية في الجزائر لإنجاز معجم ثقافي يروي تاريخ الحضارة الجزائرية بنسختين ورقية والكترونية، والذي يسعى إلى الحفاظ على الموروث الثقافي والحضاري الجزائري وكذا التعريف بالهوية الوطنية الجزائرية لابن اللغة ولغيره، وقد بينا في دراستنا التطبيقية لهذا المعجم أنه جاء كدليل ثقافي مزود بمجموعة من الصور والخرائط والأشكال والتي بينت المعجم في شكل قريب إلى الموسوعة معالجات لجذور الحضارة الجزائرية ودياناتها ولغاتها وتقاليدها منذ القدم ومنذ الدولة الأمازيغية ،كما بينا مميزات هذا المعجم من خلال الوضع والرقمنة والتي تمثلت في سهولة حفظه بالنسخة الورقية، وسهولة استخدامه في النسخة الإلكترونية بسرعة ودون عناء. This study, entitled “The Algerian Dictionary between status and digitization - the Algerian Culture Dictionary as an example - aims to demonstrate the extent of the importance of the dictionary in the Arabic language and in preserving literary, linguistic, cultural and cultural legacies. The Supreme Council for the Arabic Language in Algeria sought to complete a cultural dictionary that narrates the history of Algerian civilization in two versions. Paper and electronic, which seeks to preserve the Algerian cultural and civilizational heritage, as well as to introduce the Algerian national identity to the language user and others. We have shown in our applied study of this dictionary that it came as a cultural guide equipped with a set of pictures, maps, and shapes, which showed the dictionary in a form close to the encyclopedia, treatments of the roots of Algerian civilization. Its religions, languages and traditions since ancient times and since the Amazigh state. We also explained the advantages of this dictionary through development and digitization, which were the ease of preserving it in the paper version, and the ease of using it in the electronic version quickly and without trouble.
معجم الثقافة الجزائرية نموذجا
Keywords: معجم الثقافة الجزائرية،الرقمنة